Expressing Feelings Creatively: Integration of Visual Documentation and Reflection in English Language Learning in Elementary Schools: Penelitian - Putri Khairunnisa, Rahmahdalena; Purmasari, Siti Fatimah; Lutfiah, Nur; Ningrum, Cahaya; Musyaffa, Roshim Ahmad; Qamariah, Zaitun; Widiastuty, Hesty (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to examine the integration of visual documentation and reflection in English language learning materials.“Feelings”in elementary school students. The background of the study stems from the need for emotional vocabulary learning that not only supports language skills but also the development of children's emotional intelligence. This study used a descriptive qualitative approach involving one class of elementary school students through observation, visual documentation, and reflection notes. Data analysis was conducted using Thematic Analysis. The results showed that the use of visual media such as photos, videos, and vocabulary cards can improve students' understanding of emotional vocabulary and strengthen their engagement in learning activities. The percentage of student engagement reached 55.6 percent in the high category, and vocabulary mastery increased significantly from 30 percent to 82 percent after the activity. Students' emotional responses also developed, as seen from the increase in their ability to express emotions spontaneously from 22 percent to 74 percent. However, the study found several challenges such as the short learning duration, differences in ability between students, and technical difficulties during documentation. In conclusion, the integration of visual documentation and reflection is an effective approach to improving emotional vocabulary learning in elementary school students. This method is able to create contextual, multimodal learning and supports students' linguistic and emotional development. This research recommends the development of more varied visual media, longer learning durations, and the use of visual portfolios as part of learning evaluation.